Ethical Audit Decisions: A Structuration Perspective - Dillard, Jesse F. (Journal of business ethics, 2002)
The public accounting profession has long relied on its reputation for integrity and veracity as justification for its professional status and monopoly privilege predicated on claims of acting in the public interest. If such status and privilege are to be justified and sustained, serious consideration of what constitutes ethical behavior, how such behavior is motivated as well as an explicit recognition of the rights and interests of affected parties constitutes an ethical imperative for the profession. Traditionally, work on ethics and auditing is quite narrow, failing to recognize the social context of individual actions, failing to identify the relevant constituencies of the profession, and failing to articulate processes through which the constituencies interests can be identified. Generally, the accounting literature has taken a cognitive perspective on ethical decision making which views the resolution of ethical dilemmas as primarily a function of the moral makeup of the actor responding within the context of the Code of Professional Conduct. The purpose of this paper is to broaden the theoretical base of ethical research, specifically within the area of professional accounting and more generally in the area of business. We propose the application of structuration theory in conjunction with stakeholder theory and a responsibility ethic. The application of stakeholder theory is a means for identifying affected constituencies. A responsibility ethic recognizes the situatedness of an individual within an ongoing professional community. Structuration theory provides a theoretical framework for articulating and investigating both the structures within which action is carried out as well as the interaction between the social structures and the actors. Taken together, the theories allow for an enhanced ability to define ethical behavior within a business context and to understand the contextual antecedents and consequences of ethical acts.